The Evolution of the Islamic Calendar and The Role of Department of Islamic Development Malaysia: Insight and Implementation in Malaysia - Susiknan Azhari; Shobahussurur Shobahussurur; Mohd. Saiful Anwar Mohd Nawawi; Taufiqurohman Taufiqurohman (Al-Mazaahib: Jurnal Perbandingan Hukum, 2026)
This research explains the idea of an Islamic calendar system that grew in Malaysia as one of the Muslim countries that contributed to the falac science development in Southeast Asia. This article is a literature research with a historical approach to describe how the process of developing and adapting the Islamic calendar in Malaysia. The results shows that the system has changed five times, and the first period (before 1969-1986) used the Istilahi calendar. Meanwhile, the second (1986-1991) and third (19922-1994) periods used Ijtimak Hakiki and Ijtimak Wujudul Hilal. From 1995 to 2021, the fourth period used Imkanur Rukyat or Takwim Rukyat. In practice, the Imkanur Rukyat is similar to Imkanur Rukyat MABIMS (2,3,8). Since 1 Muharam 1443 H/2021, the fifth period employs a new criterion to determine the beginning of the lunar month, namely the MABIMS Hilal Neo-Visibility (3,6.4). Main efforts to unify the Islamic calendar in Malaysia are made by publishing the Hijri Almanac based on the MABIMS hilal visibility theory, which is used as an administrative and worship reference. The hilal observations are still carried out, and can change the dates in the almanac, as happened in the determination of beginning of Shawwal 1443 H/2022. Penelitian ini menguraikan gagasan sistem kalender Islam yang berkembang di Malaysia sebagai salah satu negara Muslim yang berkontribusi terhadap perkembangan ilmu falak di Asia Tenggara. Artikel ini merupakan penelitian pustaka dengan pendekatan historis untuk menggambarkan proses pengembangan dan adaptasi kalender Islam di Malaysia. Hasil penelitian menunjukkan bahwa sistem tersebut telah mengalami lima kali perubahan, dan periode pertama (sebelum 1969–1986) menggunakan kalender Istilahi. Sementara itu, periode kedua (1986–1991) dan ketiga (1992–1994) menggunakan Ijtimak Hakiki dan Ijtimak Wujudul Hilal. Dari tahun 1995 hingga 2021, periode keempat menggunakan Imkanur Rukyat atau Takwim Rukyat. Dalam praktiknya, Imkanur Rukyat mirip dengan Imkanur Rukyat MABIMS (2,3,8). Sejak 1 Muharam 1443 H/2021, periode kelima menerapkan kriteria baru untuk menentukan awal bulan lunar, yaitu MABIMS Hilal Neo-Visibility (3,6.4). Upaya utama untuk menyatukan kalender Islam di Malaysia dilakukan dengan menerbitkan Almanak Hijriyah berdasarkan teori visibilitas hilal MABIMS, yang digunakan sebagai acuan administratif dan ibadah. Pengamatan hilal masih dilakukan, hasilnya dapat mengubah tanggal dalam almanak, sebagaimana kasus yang terjadi dalam penentuan awal Syawal 1443 H/2022 M.